Treatment decisions and survival for people with small-cell lung cancer - Powell, H.A.; Tata, L.J.; Baldwin, D.R.; Potter, V.A.; Stanley, R.A.; Khakwani, A.; Hubbard, R.B. (Cancer Research UK, 2014)
Background: Chemotherapy improves survival for many patients with SCLC, and hence it is important to understand variations in practice and outcomes for this treatment strategy.